(untitled) (Comillas Journal of International Relations, 2019)
The cities of today are confronted with ever-increasing numbers of informal settlements. Notwithstanding four decades of national and international efforts to reverse the distressing state of affairs, slums have become the main housing type worldwide —slum formation nothing but increasing. The undermined and untapped potential that urban informality represents critically hinders human progress. Narrow approaches to slum upgrading and to informal dwellers produce insufficient and unsustainable results. The few comprehensive, multidimensional, and integral slum upgrading programs attest that a change of perspective is very much needed. To this effect, we have conceived a pyramid on the indispensable elements of slum upgrading: to illustrate our proposed methodology for attaining more sustainable, comprehensive, and humanized solutions vis-à-vis urban informality.